Endoscopy training in Australia during COVID‐19: Efficacy and knowledge assessment of gastroenterology and general surgery trainees. Issue 12 (8th November 2022) - Zorron Cheng Tao Pu, Leonardo; Cox, Daniel R A; Be, Kim H; Ng, Jonathan; Yeaman, Fiona; Gilhotra, Rajit A; Efthymiou, Marios; Vaughan, Rhys; Nestel, Debra; Perini, Marcos V; Muralidharan, Vijayaragavan; Chandran, Sujievvan
Abstract: Background and Aim: During COVID‐19, restrictions to elective endoscopy were introduced worldwide. A reduction in procedures may impact trainees' endoscopy learning. This study aims to assess Australian advanced gastroenterology and general surgery trainees' self‐perceived efficacy and knowledge in endoscopy during the pandemic. Methods: All Australian gastroenterology and general surgery trainees in their last 2 years of accredited training were invited to participate through email (2020–2021 and 2021–2022 training cycles). The primary outcome was to assess trainees' self‐efficacy and knowledge regarding gastrointestinal endoscopy. Secondary outcomes included subgroup analysis between gastroenterology and general surgery trainees. Self‐perceived efficacy was assessed with Likert‐scale questions on 20 endoscopy procedures and knowledge was assessed through 21 endoscopy‐related multiple choice questions. Results: Eighty‐one trainees responded to a self‐efficacy questionnaire and 77 responded to the knowledge questionnaire. Over 90% of the trainees were confident or extremely confident in diagnostic endoscopy, but only half demonstrated similar efficacy for therapeutic endoscopy. The efficacy for basic endoscopy procedures was higher for gastroenterology trainees (64.0% vs 51.1%, P  < 0.001). Last‐year trainee achievement of conjoint committee requirements for upper gastrointestinal endoscopy was achieved in 95.8% of gastroenterology trainees versus 22.2% of surgical trainees ( P  < 0.001). The median score on the knowledge questionnaire was also higher for the gastroenterology subset (90.5% vs 71.4%, P  < 0.001). Conclusion: During COVID‐19, endoscopy trainees' self‐efficacy in endoscopic diagnostic procedures was achieved for most trainees. The differences in self‐perceived efficacy and knowledge between gastroenterology and surgical trainees may be reflective of the different opportunities for learning between the two groups. Abstract : During COVID‐19, restrictions to elective procedures were introduced worldwide. Our study aimed to assess Australian advanced Gastroenterology and General Surgery trainees' self‐perceived efficacy and knowledge in endoscopy during the pandemic. We have found that although self‐efficacy in endoscopic diagnostic procedures was achieved for most trainees, differences in self‐perceived efficacy and knowledge were shown between gastroenterology and surgical trainees and may be reflective of the different opportunities for learning between the two groups.